Impact of the interval between coronary angiography and off-pump coronary bypass surgery on postoperative renal function - Na-young Kim; So Yeon Kim; Na Hyung Lee; Young Lan Kwak (Korean Journal of Anesthesiology, 2010)
BackgroundPostoperative acute kidney injury (AKI) is a significant complication after coronary artery bypass surgery. Prior coronary angiography increases the likelihood of AKI due to the use of a radiocontrast dye. This study examined the effect of coronary angiography on the postoperative renal function after off-pump coronary artery bypass surgery (OPCAB).MethodsThe records of 110 patients who required OPCAB were reviewed. These patients also had at least two of the following conditions: chronic kidney disease, hypertension, diabetes mellitus, emergency surgery, congestive heart failure, age >75 years, hematocrit <30%, a left ventricular ejection fraction <40%, or the use of angiotensin-converting enzyme inhibitors or angiotensin receptor blockers. The patients were divided into two groups; coronary angiography performed within two days of OPCAB (Control group, n = 55), and coronary angiography performed more than two days before OPCAB (Angio group, n = 55). The serum creatinine (SCr) and serum cystatin C levels were measured on the day before surgery, as well as on postoperative days 1, 2, 3 and 7. The estimated glomerular filtration rate (eGFR) was also obtained on those days. AKI was defined as an increase in Cr ≥50% or ≥0.3 mg/dl within 48 hours.ResultsThe postoperative changes in the SCr, cystatin C and eGFR were similar in the two groups. The incidence of AKI and renal replacement therapy were similar in the two groups.ConclusionsCoronary angiography performed within two days of OPCAB does not affect the postoperative renal function.